Promoting idea exploration and harmonization in the creative process: cultivating interdependence and employees' perspective-Taking are key. Issue 4 (4th July 2022) - Ng, Thomas W. H.; Koopmann, Jaclyn; Parker, Sharon K.
ABSTRACT: While the creative approach of idea exploration (e.g., consideration of multiple alternatives, doing in-depth research) has been identified to be important in the creative process, another approach, idea harmonization (e.g., avoidance of disruptive ideas, endorsement of co-worker ideas), has been largely overlooked. This study is the first to examine both approaches. We propose that, to engage in both idea exploration and harmonization, employees need to seek to understand co-workers' thoughts and feelings. Thus, organizations desiring both creative approaches from their employees may consider crafting the workplace to promote employees' relational skills, especially perspective-taking. One way to do so is to enhance social and task interdependence among employees. Through a mixed-level longitudinal design, we showed that both social and task interdependence were positively related to employee perspective-taking and that perspective-taking was positively related to both idea exploration and harmonization. Crucially, we also found evidence that creative requirement attenuated this sequence. Altogether, this study highlights a new work design pathway to potentially promote creativity: greater social and task interconnections amongst employees are associated with more engagement in perspective-taking, especially when creativity is not explicitly demanded. Greater perspective-taking, in turn, is related to employees more fully exploring and harmonizing ideas.